Computation of isomorphisms of coherent configurations - Miyamoto, Izumi (Ars mathematica contemporanea, 2010)
A program computing isomorphisms between association schemes was applied to speed up the computation of normalizers of permutation groups. A transitive permutation group forms an association scheme while a permutation group which may not be transitive forms a coherent configuration. In this paper we discuss the extension of the above program to compute isomorphisms between coherent configurations and show some typical examples of computing normalizers.
Keywords: matematika; permutacijske grupe